KAJIAN TENTANG PERANCANGAN APLIKASI PENDETEKSI SEL DARAH PUTIH MENGGUNAKAN METODE COLOR HISTOGRAM - Alvin Christo Tjiptiadi; Lina Lina; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
We developed a white blood cell detection system using Color Histogram method. The images which are taken automatically by a servo motor consist of the red blood cells and the white blood cells. The white blood cells’ positions are detected based on their RGB color intensities. The main target of the system is to detect the location of the white blood cells in a given blood cell pictures.